If it's not what You are looking for type in the equation solver your own equation and let us solve it.
39=-3+5(x+6)
We simplify the equation to the form, which is simple to understand
39=-3+5(x+6)
Reorder the terms in parentheses
39=-3+(+5x+30)
Remove unnecessary parentheses
+39=-3+5x+30
We move all terms containing x to the left and all other terms to the right.
-5x=-3+30-39
We simplify left and right side of the equation.
-5x=-12
We divide both sides of the equation by -05 to get x.
x=2.4
| 7w+8=64 | | 2x-5=-(3x+7) | | 3=-6x+3(x+3) | | 19-3x=9x-5 | | 1.8+7n=4n | | y+6=5x+3xr-4 | | 9-3p=3 | | 7x+-3=-11 | | 2-7x=5x+50 | | 2x=-(3x+7) | | 25m-10=21m+14 | | 10y-7=28+3y | | -122+2x=153-9x | | 8-3w=5 | | 3x-14=-5x+34 | | 16=7b+30 | | 0.70x=455000 | | 3u-12=-21 | | 4*7v= | | 8y-3=-27 | | 3z^2+3z+1=0 | | 2x^2-3x-72=0 | | 30y^2=36y | | 2(a-8)+7=5(a+2)-3a-29 | | 9x-45=5x+135 | | (2)(5)+4= | | -3x-9+8x=12x+9-7x | | solvea+4=10 | | 6x+11=-4-3x | | 3x-14=7x-10 | | 18=10e^4x | | z+29=47 |